A rare threat to patients with hematological malignancies: Saprochaete clavata - Elif Özge Damar Mıdık; Ayşe Batırel; Serap Demir Tekol (Journal of Global Antimicrobial Resistance)
Background: Opportunistic infections, especially fungal pathogens, are an important cause of morbidity and mortality in patients suffering from hematological malignancies. Nevertheless, over the last decade, less common fungal species that causes serious fungemia or disseminated fungal infections such as Saprochaete spp and Trichosporon spp. have emerged. Saprochaete infection has very rarely been identified as an invasive pathogen in humans. Because of the high mortality rate (65%) and intrinsic resistance to echinocandins, early recognition and treatment of this infection is very important The aim of this case series is to evaluate the clinical features and treatment of three cases of Saprochaete clavata bloodstream infection, followed in our hospital between 2021 and 2023. Cases: The mean duration of severe neutropenia was 54,6 days. The mean duration of profound neutropenia (<100 neutrophils/mm3) at the time of positive culture was 12,6 days. All patients had grade 3 mucositis. Clinical features, laboratory findings and treatment are outlined in Table 1 and Table 2.Colonies of Saprochaete clavata and microscopic image are shown in figuresOne patient recovered, the other two patients died. Conclusion: Profound neutropenia, cytotoxic chemotherapy and the presence of central venous catheters have been determined as risk factors for S.clavata infection.If these fungi are suspected in hematological malignant patients, it is important to carefully select empiric antifungal therapy because they are resistant to echinocandins. Prompt initiation of antifungal therapy is vital to decrease mortality.